EFFECTS OF SURNAME FAMILIARITY ON RECALL - Kolic-Vehovec, Svjetlana; Arar, Ljiljana (Studia psychologica, 2005)
The effects of the familiarity of surnames and words on recall of surnames-words differently prompted, either by a "surname" label or by pairing surname with name were examined. It was found that in a between-subjects design the familiarity of surnames that were non-words showed positive effects on recall when surnames were prompted by the "surname" label. The familiarity of surnames that were words influenced recall positively only in a within-subjects design. When a surname was prompted by a "surname" label, a combined effect of familiarity of items as surnames and as words on surname recall was obtained. When first names were added to surnames, the familiarity of the surnames was a more important factor in recall than familiarity of words. We conclude that the effects of the familiarity of surnames and words on recall of surname-words might be due to the surname context as well as to the type of the experimental design. [PUBLICATION ABSTRACT]